Awakening your ikigai : how the Japanese wake up to joy and purpose every day - Mogi, Ken'ichirō, 1962- (The Experiment, 2018)
Ikigai is a Japanese phenomenon commonly understood as "your reason to get up in the morning." Ikigai can be small moments: the morning air, a cup of coffee, a compliment. It can also be deep convictions: a fulfilling job, lasting friendships, balanced health. Whether big or small, your ikigai is the path to success and happiness in your own life.